2010
DOI: 10.3758/mc.38.8.1058
|View full text |Cite
|
Sign up to set email alerts
|

Working memory and target-related distractor effects on visual search

Abstract: We examined two forms of top-down effects on visual selection: (1) information held in working memory (WM) and (2) the semantic relations between targets and distractors. We found that items held in WM affected search for a different target. This WM-based interference effect generalized across different exemplars, even though participants could remember the specific exemplar on the trial. This argues against a memory top-up account of performance. In addition, there was interference from distractors that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 35 publications
6
30
0
Order By: Relevance
“…There is a substantial body of work on the interaction of working memory and visual search (Poole & Kane, 2009; Sobel, Gerrie, Poole, & Kane, 2006). Holding an item in working memory influences the course of visual search (Balani, Soto, & Humphreys, 2010; Luria & Vogel, 2011; Olivers, Peters, Houtkamp, & Roelfsema, 2011; Soto, Heinke, Humphreys, & Blanco, 2005) (and vice versa (Eriksen, Eriksen, & Hoffman, 1986)). This leads to the hypothesis that the representation of the target (“search template”) resides in working memory, perhaps in an “active” subset of that working memory (Beck, Hollingworth, & Luck, 2011; Olivers et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There is a substantial body of work on the interaction of working memory and visual search (Poole & Kane, 2009; Sobel, Gerrie, Poole, & Kane, 2006). Holding an item in working memory influences the course of visual search (Balani, Soto, & Humphreys, 2010; Luria & Vogel, 2011; Olivers, Peters, Houtkamp, & Roelfsema, 2011; Soto, Heinke, Humphreys, & Blanco, 2005) (and vice versa (Eriksen, Eriksen, & Hoffman, 1986)). This leads to the hypothesis that the representation of the target (“search template”) resides in working memory, perhaps in an “active” subset of that working memory (Beck, Hollingworth, & Luck, 2011; Olivers et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using more complex objects have yielded only mixed results regarding the degree to which attentional capture is dependent on the visual similarity between the WM item and the irrelevant distracters in the search display. One study (Bahrami Balani, Soto, & Humphreys, 2010) found guidance towards distracters that were exemplars of the same category as the WM item. There was also some evidence that distracters that were semantically associated with the WM item captured attention.…”
Section: Introductionmentioning
confidence: 99%
“…In these experiments, both the WM item and the target stimulus tend to rely on similar representations, i.e. they are both objects, in some cases even objects from the same superordinate category (Bahrami Balani et al, 2010). Thus, it can be difficult to disentangle the effects of WM-guided capture and capture by the target-related attentional set.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For visual and memory set sizes in the range of 1–4 characters, search times are roughly linear with the product of visual and memory set sizes (Schneider & Shiffrin, 1977). More recent work paints a complicated picture of the effects of working memory loads on visual search (Balani, Soto, & Humphreys, 2010; Downing & Dodds, 2004; Han & Kim, 2004; Woodman, Vogel, & Luck, 2001) (Olivers, Peters, Houtkamp, & Roelfsema, 2011) but as a general rule these are studies in which working memory is pitted against search. We do not know how memory and vision work together when stimuli are drawn from the wide set of visual objects beyond alphanumeric characters nor what happens when the numbers of task relevant items held in memory gets well beyond the limits of working memory.…”
mentioning
confidence: 99%